BIOAKUMULASI LOGAM BERAT DALAM MANGROVE RHIZOPORA MUCRONATA DAN AVICENNIA MARINA DI MUARA ANGKE JAKARTA - Handayani, Titin (Jurnal Teknologi Lingkungan, 2006)
Mangrove area in Muara Angke was dominated by api-api (Avicenniamarina) and bakau (Rhizophora mucronata). We asume that thesespecies was able to acumulate h eavy metals, since both of them haveadapted in this environmental condition which content of highconcentration h eavy metals. The objective of this experiment was toanalyze heavy metals content in the tissue of api-api (Avicennia marina)and bakau (Rhizophora mucronata) in Muara Angke Jakarta. The resultsshowed that Cu was highest heavy metal content in root of bakau(24.431 ppm) . While 23.674 ppm of Cu was content in api-api roots. Cucontent in sediment was 26,640 ppm.